Biochemical responses in lettuce subjected to salinity and the application of purple lettuce extract - Deuner, Cristiane; Meneghello, Géri Eduardo; Castellanos, César Iván Suarez; Borges, Carolina Terra; Deuner, Sidnei (Scientia Plena, 2020)
Antioxidants are substances that present in low concentrations, compared to the oxidizable substrate, significantly delay or inhibit the oxidation of the substrate, which can be induced by several stress factors, such as salinity. The purple varieties of lettuce have high antioxidant activity because of the large amount of anthocyanins they possess. The objective of this study was to analyze biochemical responses in lettuce seedlings submitted to saline stress and to the application of aqueous extract of leaves of purple lettuce. Seeds of lettuce, cv. Regina, which were cultivated in polystyrene trays, being submitted to irrigation with extracts of purple lettuce and saline solutions during the early stages of seedling development. The parameters evaluated were: chlorophyll index, flavonoids, anthocyanins and nitrogen balance, sodium content, osmotic potential, hydrogen peroxide, lipid peroxidation and enzyme activity superoxide dismutase, ascorbate peroxidase and catalase. The extract of purple lettuce leaves is efficient to reduce oxidative stress in lettuce seedlings, in saline environment.